2023
DOI: 10.3390/ma16155429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Properties of Structural Lightweight Concrete with Sintered Fly Ash Aggregate in Terms of Its Suitability for Use in Prestressed Members

Abstract: The main aim of the paper was to assess whether the lightweight concrete with a new type of sintered fly ash aggregate can be used as a structural material for post-tensioned elements subject to high effort. This purpose was achieved by comparison of the properties of lightweight aggregate concrete with Certyd aggregate (LWAC) and normal-weight concrete with dolomite aggregate (NWAC) of similar strength in terms of their suitability for use in prestressed members. Special emphasis was placed on long-term, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, Lopez et al [55] showed that high-performance LWCs mixed with expandedslate LWAs exhibited less creep and slightly greater shrinkage than the general HPC of a similar paste, mix design, and strength. Rodacka et al [56] showed that the final value of the test for the shrinkage deformation of LWCs was 38% lower than the value estimated according to Eurocode EN-1992-1-1 [57]. Furthermore, the final creep deformation of the tested LWCs was more than two times lower than that of the corresponding NCs.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, Lopez et al [55] showed that high-performance LWCs mixed with expandedslate LWAs exhibited less creep and slightly greater shrinkage than the general HPC of a similar paste, mix design, and strength. Rodacka et al [56] showed that the final value of the test for the shrinkage deformation of LWCs was 38% lower than the value estimated according to Eurocode EN-1992-1-1 [57]. Furthermore, the final creep deformation of the tested LWCs was more than two times lower than that of the corresponding NCs.…”
Section: Introductionmentioning
confidence: 94%
“…The difference in ductility index in NWAC and LWAC is 20% where the LWAC showed increased ductility. This is because fibers may span one another and continuously withstand deformation (20) . The LWAC although has lesser tensile strength, the impact test proved that it is no longer inferior to that of NWAC.…”
Section: Ductility Indexmentioning
confidence: 99%